2009
DOI: 10.2319/060208-288.1
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Resistance in Self-Ligating Orthodontic Brackets and Conventionally Ligated Brackets

Abstract: Objective:To compare the amount of expressed frictional resistance between orthodontic selfligating brackets and conventionally ligated brackets in vitro as reported in the literature. Methods: Several electronic databases (Medline, PubMed, Embase, Cochrane Library, and Web of Science) were searched without limits. In vitro studies that addressed friction of self-ligating brackets compared with conventionally ligated brackets were selected and reviewed. In addition, a search was performed by going through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 35 publications
1
37
0
5
Order By: Relevance
“…It allows for passive trapping of the wire (except in the interactive brackets with larger diameter wires) without the involvement of any outside connecting agent and allows the use of lighter forces due to reduced friction, which helps to preserve the anchorage 3,9,10,14,17,18,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows for passive trapping of the wire (except in the interactive brackets with larger diameter wires) without the involvement of any outside connecting agent and allows the use of lighter forces due to reduced friction, which helps to preserve the anchorage 3,9,10,14,17,18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…With the frequent use of sliding mechanics in Orthodontics, friction control has become a major concern for successful treatment [1][2][3][4] . The use of forces below values required for tooth movement prolongs treatment time.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was little evidence to claim an advantage with large rectangular wires. Also, it was reported that friction in both bracket types increased as the archwire size increased [Ehsani et al, 2009]. Another important factor to consider is resistance to sliding.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient evidence could not be found to claim that with large rectangular wires, in the presence of tipping and/or torque and in arches with considerable malocclusion, self-ligating brackets produce lower friction compared with conventional brackets. 17 For many years arguments has raged over whether the fluid media is a lubricant or an adhesive when a bracket is slid through an archwire. In vitro studies have demonstrated friction to be more in dry state as compared to wet states.…”
Section: Discussionmentioning
confidence: 99%